PEMETAAN PENYEBARAN DAN PREDIKSI JUMLAH PENDUDUK MENGGUNAKAN MODEL GEOMETRIK DI WILAYAH BANDAR LAMPUNG BERBASIS WEB-GIS - Rahayu, Yuni; Muludi, Kurnia; Hijriani, Astria (Jurnal Komputasi, 2016)
Population distribution patern is one of Bandar Lampung government concerns. This information is useful for goverment decision making for specific local development.The prediction of population number using certain model is predicted will be useful for Bandar Lampung development plan.Â  Information about distribution and prediction of resident population in Bandar Lampung are processed manually and limitedly presented in form of tables and graphs. The purpose of this research is to build Bandar Lampung web based Geographic Information System that predict population distribution and mapping using Geometric Model. Data in this research were obtained from Statistics Of Bandar Lampung Municipality Publication. This system was implemented by using QGIS, GeoServer, PostgreSQL and PHP programming language. Overall,the testing results show that the system is appropriate and functional.Keywords: Geographic information system, Geometric Model, Mapping population.